Isolation and characterization of multi-potential Rhizobium strain ND2 and its plant growth-promoting activities under Cr(VI) stress. Issue 8 (3rd July 2017) - Karthik, Chinnannan; Oves, Mohammad; Sathya, Kumar; Sri Ramkumar, Vijayan; Arulselvi, Padikasan Indra
ABSTRACT: Soil contaminated by chromium (Cr) is a major concern for sustainable agriculture. Considering this as a basis, the present study was designed to isolate Cr(VI)-reducing and plant growth-promoting bacterial strain from contaminated sampling sources. In this study, Rhizobium strain ND2 was isolated from the root nodules of Phaseolus vulgaris grown in leather industrial effluent contaminated soil. The strain ND2 exhibited strong resistance to different heavy metals and reduced 30 and 50 µg ml −1 concentrations of Cr(VI) completely after 80 and 120 h of incubation, respectively, as well as chromium adsorption and immobilization were confirmed by scanning electron microscopic equipped with energy X-ray spectroscopy. In addition, the strain produced 21.73 and 36.86 µg ml −1 of indole-3-acetic acid at 50 and 100 µg ml −1 of L-tryptophan supplimentations, respectively. Strain ND2 positively affected the exo-polysaccharide, ammonia, protease and catalase production and stimulated root length of various test crops under Cr(VI) stress. Moreover, Rhizobium strain ND2 has the potential to colonize the diverse agricultural crops. Thus, the present findings strongly suggested that the multipotential properties of ND2 could be exploited for bioremediation of contaminated sites with Cr(VI) as well as potential bio fertilizer for enhancing the agricultural productivity.